1972
DOI: 10.1103/physrevb.5.3292
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Propagation, Stress Effects, and Interaction Parameters at the Displacive Transition in SrTiO3

Abstract: The interaction between strain and order parameter at the structural transition in SrTi03 is investigated by ultrasonic measurements of attenuation, velocity shifts, and stress dependence of the transition temperature T, . A method is described by which measurements of domain attenuation are used to correct the velocity data below T,. Also, biaxial pressure has been successfully used to suppress the domain structure in the tetragonal phase. By comparing the experimental results with the consequences of aphenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 29 publications
4
29
2
1
Order By: Relevance
“…Phase changes with temperature appear to have no effect on strontium coordination in this set of compounds. For example, SrTiO 3 (s) undergoes a ferroelastic phase transition (so-called "soft mode") from a cubic to a tetragonal space group at T c = 105 K. Previous work has shown that this does not affect unit cell volume or significantly change atom positions around strontium, consistent with our fit results (29,37,38).…”
Section: Static and Anharmonic Disorder In Strontium Compoundssupporting
confidence: 89%
“…Phase changes with temperature appear to have no effect on strontium coordination in this set of compounds. For example, SrTiO 3 (s) undergoes a ferroelastic phase transition (so-called "soft mode") from a cubic to a tetragonal space group at T c = 105 K. Previous work has shown that this does not affect unit cell volume or significantly change atom positions around strontium, consistent with our fit results (29,37,38).…”
Section: Static and Anharmonic Disorder In Strontium Compoundssupporting
confidence: 89%
“…The CT transition temperature T a is known to be pressure dependent. Measured by different groups, this dependence of T a was found to be 17 K/GPa [40], 29 K/GPa [41,42], and 5 K/GPa [42] for hydrostatic pressure, and 180 K/GPa under uniaxial pressure [40] by ultrasonic resonance. We can relate these values to the effect of the epitaxial stress on the transition temperature in our case.…”
Section: Ct Phase Transition For Srtio 3 Crystals Covered With Ybco Amentioning
confidence: 99%
“…Though the elastic and anelastic properties of the SrTiO 3 crystal in a vicinity of T C are investigated within more than 25 years [2][3][4], however, experiments were in most cases carried out at high frequencies ( f > 10 MHz). Only recently a number of papers was published [5][6][7], in which acoustic properties of SrTiO 3 were studied using low frequency experiments ( f = 1-20 Hz).…”
Section: Introductionmentioning
confidence: 99%